Refuge in the sāqya: Irrigation canals as habitat for one of the world's 100 most threatened species. (October 2019) - Sousa, Ronaldo; Teixeira, Amílcar; Benaissa, Hassan; Varandas, Simone; Ghamizi, Mohamed; Lopes-Lima, Manuel
Abstract: Anthropogenic habitats may function as a refuge for some species, including freshwater mussels (Bivalvia, Unionida). In this study we assessed possible differences in density, size and condition index of the Moroccan freshwater pearl mussel Pseudunio marocanus (Pallary, 1918), formerly Margaritifera marocana, colonizing anthropogenic (sāqya = irrigation canal) and natural (Bouhlou River) habitats in Morocco. Results showed that the individuals colonizing the irrigation canal located on the left bank have a significantly higher density and condition index when compared to natural conditions, but no differences were found regarding size. Since this species is listed as critically endangered by the IUCN, being also considered among the 100 most endangered organisms in the planet, the presence of P . marocanus in anthropogenic habitats has high conservation importance. In fact, and despite no Moroccan freshwater pearl mussels were found on the irrigation canal located in the right bank, the one located on the left bank present stable conditions for the settlement of juveniles and, if managed carefully, for the future survival of the species. However, local authorities reported frequent dredging and cleaning activities by local farmers on this sāqya without any special attention devoted to Moroccan freshwater pearl mussels (or any other species) conservation. Therefore, the results reported here can be used by scientists, managers, politicians and local people to promote future management actions that enhance the Moroccan freshwater pearl mussel protection and guarantee their future survival, including on anthropogenic habitats. Highlights: We evaluate the importance of anthropogenic habitats for a rare species. Higher density and CI was found in canals than in natural habitats. Irrigation canals provide stable conditions for Moroccan pearl mussels. Management actions to protect pearl mussels should be urgently taken.